Validity of diagnostic criteria for temporomandibular joint disorder in the diagnosis of disc displacement disorders of temporomandibular joint - Shikha N Goyal; Freny R Karjodkar; Kaustubh Sansare (Contemporary Clinical Dentistry, 2020)
Objective: The objective of this study is to assess the validity Diagnostic Criteria for Temporomandibular joint Disorder (DC/TMD) in the diagnosis of disc displacement (DD) disorders of temporomandibular joint (TMJ). Study Design: It was a prospective study in which total of 55 patients accounting to 110 TMJ; with clinical diagnosis of DD disorder as per DC/TMD criteria and all above age of 18 years were included. All the patients with clinical diagnosis of DD disorder were advised MRI. All the MRI scans were read by single radiologist. Clinician and Radiologist were blinded to each others findings. MRI diagnosis and clinical diagnosis were compared and results were formulated. Results: The use of the Kappa statistic test indicated a good diagnostic agreement (k = 0.68) between the clinician and the radiologist. The DC/TMD criterion was found to have good validity and reliability in the diagnosis of DD disorders with sensitivity of 91.57% and specificity of 77.78%. The positive predictive value and negative predicted value calculated were 92.68% and 78%, respectively. The positive and negative likelihood ratio found was 4.12 and 0.11, respectively. Conclusion: DC/TMD is a simple, reliable, valid, cost-effective tool in the diagnosis of DD disorders.